1986
DOI: 10.1111/j.1365-2885.1986.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the arrhythmogenic dose of epinephrine (ADE) following xylazine administration to halothane‐anesthetized dogs

Abstract: The arrhythmogenic dose of epinephrine (ADE) was determined in six dogs during halothane (1.35%) anesthesia before and after xylazine administration (1.1 mg/kg, i.v. bolus; 1.1 mg/kg/hr, i.v. infusion). The arrhythmogenic dose was determined by constant infusion of freshly mixed epinephrine (100 microgram/ml). The ADE was defined as the total dose of epinephrine which produced four or more intermittent or continuous premature ventricular contractions within a 15-sec period. Total dose was calculated as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several studies and case reports emphasize the cardiac complications that can arise from Xylazine use, such as biventricular systolic failure, valvular dysfunction, and myocardial necrosis and fibrosis [55][56][57]. In some cases, clinical treatment with nifedipine has been found effective in managing these cardiac complications [58]. In addition to its impact on the cardiovascular system, Xylazine has been linked to pulmonary issues.…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…Several studies and case reports emphasize the cardiac complications that can arise from Xylazine use, such as biventricular systolic failure, valvular dysfunction, and myocardial necrosis and fibrosis [55][56][57]. In some cases, clinical treatment with nifedipine has been found effective in managing these cardiac complications [58]. In addition to its impact on the cardiovascular system, Xylazine has been linked to pulmonary issues.…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…Values are reported as means & standard error. The ADE (pg/kg) for H, HG, I, and IG were 1.53 f 0.08, 3.37 f 0.46, 1.6 1 t 0.2 1, and > 15.00, respectively. Heart rates (HRs) (beats/min) and systolic pressures (mmHg) at the time of arrhythmia formation for H, HG, I, and 1G were (60.3 f 4.0 and 142.0 +.…”
mentioning
confidence: 93%
“…The oxygen requirements of a horse must be increased by the work necessary for it to regain its feet, but whether residual medetomidine limited this pony's normal physiological responses to the additional requirement is not known. Another possible cause of a cardiac arrest when an animal is recovering from anaesthesia could be adrenaline‐induced arrhythmias (Tranquilli and others 1986). Hayashi and others (1991) have shown that in dogs dexmedetomidine reduces the risk of this occurring under halothane anaesthesia.…”
Section: Discussionmentioning
confidence: 99%